Use of a handheld Doppler to measure brachial and femoral artery occlusion pressure - Vehrs, Pat R.; Richards, Shay; Blazzard, Chase; Hart, Hannah; Kasper, Nicole; Lacey, Ryan; Lopez, Daniela; Baker, Luke (Frontiers in Physiology, 2023)
Objective: Measurement of arterial occlusion pressure (AOP) is essential to the safe and effective use of blood flow restriction (BFR) during exercise. Use of Doppler ultrasound (US) is the 'gold standard' method to measure AOP. Validation of a handheld Doppler (HHDOP) device to measure AOP could make the measurement of AOP more accessible to practitioners in the field. The purpose of this study was to determine the accuracy of AOP measurements of the brachial and femoral arteries using a HHDOP. Methods: We simultaneously measured AOP using a 'gold standard' US and a HHDOP in the dominant and non-dominant arms (15 males; 15 females) and legs (15 males; 15 females). Results: There were no differences in limb circumference or limb volume in the dominant and non-dominant arms and legs between males and females or between the dominant and non-dominant arms and legs of males and females. The differences between US and HHDOP measures of AOP in the dominant and nondominant arms and legs were either not significant or small (<10 mmHg) and of little practical importance. There were no sex differences in AOP measurements of the femoral artery (p > 0.60). Bland-Altman analysis yielded an average bias (-0.65 mmHg; -2.93 mmHg) and reasonable limits of agreement (±5.56 mmHg; ±5.58 mmHg) between US and HHDOP measures of brachial and femoral artery AOP, respectively. Conclusions: The use of a HHDOP yielded acceptable measures of AOP of the brachial and femoral arteries and can be used to measure AOP by practitioners for the safe and effective use of BFR. Due to the potential differences in AOP between dominant and non-dominant limbs, AOP should be measured in each limb.